DEVELOPING LOCAL WISDOM-BASED READING TEXTS FOR ELEMENTARY SCHOOL STUDENTS: AN ADDIE-BASED MATERIALS DEVELOPMENT STUDY - Treesly Yumiardi Normin Adoe; Vera Rosalia Bulu; Nurul Fatehah Binti Norhazaruddin (Sensei International Journal of Education and Linguistic, 2025)
The reading texts in elementary school are mostly taken from the textbook and the contents are often far from the daily life of the students, so the students are not interested. Actually every region in Indonesia has local wisdom that can be made into reading texts. This study discusses the development of local wisdom-based reading texts for elementary school students. The study used research and development with the ADDIE model. The data were collected through interviews, expert validation, and also a test to the students. The result shows that the reading texts that were developed are valid, practical, and effective, and the students are more enthusiastic because the story is about their own region. Therefore, teachers are suggested to use local wisdom-based reading texts.